The people of Calicut: objects, texts, and images in the Age of Proto-Ethnography - Christian Feest (Bol. Mus. Para. Emílio Goeldi. Cienc. Hum., Belém, 2014)
Some early sixteenth-century works by artists from southern Germany (Albrecht Dürer, Hans Burgkmair, Albrecht Altdorfer, Jörg Breu) representing the ‘people of Calicut’ (which was then supposed to be accessible from Europe both in an eastward and westward direction) are explored in terms of their combination of images from South Asia and artifacts from Brazil. This is placed in the context of the methodologies developed during this period for collecting and processing data in the form of texts, images, and collections of material objects, which are considered to have been the antecedents of modern ethnography and anthropology.